Does Job Satisfaction Help in Understanding Automotive Employees’ Turnover Intention? - Giri, Vijai N.; Pavan Kumar, S.; Rajesh, Vishnukant (Prabandhan: Indian Journal of Management, 2017)
The present paper explored the mediation effect of job satisfaction (JS) on the relationship between subjective well-being (SWB), affective organizational commitment (AOC), employee performance (PRFM), and turnover intention (TI). Data were collected from 457 employees working in various automotive industries across India. Structural equation modelling (SEM) technique using WarpPLS 5.0 was used to verify the proposed hypotheses. The results revealed that SWB, AOC, and JS significantly influenced employee turnover intention and JS acted as a potential mediator between SWB, AOC, PRFM, and TI. The findings are pertinent for the managers of the automotive industries since it would help them to reduce employee turnover intention. Implications of the findings were discussed in greater detail in the discussion section of the paper.